Influence of individual bracket base design on the shear bond strength of in-office 3D printed brackets: an in vitro study - Hodecker, Lutz; Scheurer, Mats; Scharf, Sven; Roser, Christoph; Fouda, Ahmed M.; Bourauel, Christoph; Lux, Christopher J.; Scheurer, Carolien A. J. (Journal of Functional Biomaterials, 2023)
(1) Background: Novel high-performance polymers for medical 3D printing enable in-office manufacturing of fully customized brackets. Previous studies have investigated clinically relevant parameters such as manufacturing precision, torque transmission, and fracture stability. The aim of this study is to evaluate different design options of the bracket base concerning the adhesive bond between the bracket and tooth, measured as the shear bond strength (SBS) and maximum force (Fmax) according to DIN 13990. (2) Methods: Three different designs for printed bracket bases were compared with a conventional metal bracket (C). The following configurations were chosen for the base design: Matching of the base to the anatomy of the tooth surface, size of the cross-sectional area corresponding to the control group (C), and a micro- (A) and macro- (B) retentive design of the base surface. In addition, a group with a micro-retentive base (D) matched to the tooth surface and an increased size was studied. The groups were analyzed for SBS, Fmax, and adhesive remnant index (ARI). The Kruskal-Wallis test with a post hoc test (Dunn-Bonferroni) and Mann-Whitney U test were used for statistical analysis (significance level: p < 0.05). (3) Results: The values for SBS and Fmax were highest in C (SBS: 12.0 ± 3.8 MPa; Fmax: 115.7 ± 36.6 N). For the printed brackets, there were significant differences between A and B (A: SBS 8.8 ± 2.3 MPa, Fmax 84.7 ± 21.8 N; B: SBS 12.0 ± 2.1 MPa, Fmax 106.5 ± 20.7 N). Fmax was significantly different for A and D (D: Fmax 118.5 ± 22.8 N). The ARI score was highest for A and lowest for C. (4) Conclusions: This study shows that conventional brackets form a more stable bond with the tooth than the 3D-printed brackets. However, for successful clinical use, the shear bond strength of the printed brackets can be increased with a macro-retentive design and/or enlargement of the base.
Gesehen am 18.08.2023